Molecular Phylogenetic study on Chingia Sphaerostephanoschristella groups of Genera (Thelypteridaceae) using Rbcl. Gene Sequences data from Sabah - Idris Mohd Said; Nazirah Mustaffa (Universiti Malaysia Sabah, 2010)
This study determined the phylogenetic relationship of Chingia, Sphaerostephanos and Christella groups of genera. The study sites consisted of Crocker Range Park and few of the West Coast Sabah area. In this phylogenetic study, rbcl gene marker was used to infer phylogenetic relationships of the study groups. In the phylogenetiC study of Chingia, Sphaerostephanos and Christella groups, 977 base pairs of DNA sequences were obtained from 32 samples representing the 3 groups of genera. The phylogenetiC relationships revealed that Sphaerostephanos is a taxonomically-problematic group especially for Pronephrium and Sphaerostephanos. The phylogenetic analyses found that there were two clades derived from the primitive Sphaerostephanos group, consisted of a monophyly advanced Sphaerostephanos clade and a monophyly clade of Chingia group and Christella group. It was found that some of the Christella spp. (C subpubescens and C papilio) were established a lineage to Chingia group in the rbcl analyses. The grouping of Chingia and Plesioneuron into the Chingia were not completely supported by the rlxl analyses since Chingia spp. (C clavipilosa and C perrigida) were clustered into Christella group. Chingia and Christe//a were found to form a monophyletic clade together in both analyses. However, rbcl analyses does not support this grouping very well with <70% of bootstrap probability, and showed that Chingia group and Christella group were almost separated into two independent monophyly clade. It can be seen that Chingia group and Christella group were derived from a monophyletic group together and gradually evolved to form two independent groups. Pneumatopteris was verified being the genera under the Sphaerostephanos group since Pneumatopteris was found appear in the monophyletic advanced Sphaerostephanos clade in the rbcl analyses. Despite being that, the grouping of genera within Sphaerostephanos group cannot be displayed clearly. This could be due to the insufficiency of morphological characters used in morphological analyses were not strong enough to separate or distinguish certain genera into the Sphaerostephanos group. Genetic factors were also believed to influence the outcomes of rbcl analyses on the Sphaerostephanos group. Undoubtedly, more details studies should be carried out to support the proposed conclusions since this is the first time phylogenetic study conducted on Chingia, Sphaerostephanos and Christella groups of genera.